Detection of pseudorabies virus antibody in swine serum and oral fluid specimens using a recombinant gE glycoprotein dual-matrix indirect ELISA. (November 2021) - Cheng, Ting-Yu; Magtoto, Ronaldo; Henao-Díaz, Alexandra; Poonsuk, Korakrit; Buckley, Alexandra; Van Geelen, Albert; Lager, Kelly; Zimmerman, Jeffrey; Giménez-Lirola, Luis
Pseudorabies (Aujeszky disease) virus (PRV) was eliminated from domestic swine in many countries using glycoprotein E (gE)-deleted vaccines and serum antibody gE ELISAs, but PRV continues to circulate in some regions and in most feral swine populations in the world. We created a dual-matrix (serum and oral fluid) indirect IgG gE ELISA (iELISA) and evaluated its performance using samples from 4 groups of 10 pigs each: negative control (NC), vaccination (MLV), PRV inoculation (PRV), and vaccination followed by challenge (MLV-PRV). All serum and oral fluid samples collected before PRV challenge and all NC samples throughout the study were negative for gE antibodies by commercial blocking ELISA (bELISA) and our iELISA. Nasal swab samples from 9 of 10 animals in the PRV group were gB quantitative PRC (qPCR) positive at 2 days post-inoculation (dpi). The oral fluid iELISA detected a significant S/P response in the PRV ( p = 0.03) and MLV-PRV ( p = 0.01) groups by 6 dpi. ROC analyses of serum bELISA ( n = 428), serum iELISA ( n = 426), and oral fluid iELISA ( n = 247) showed no significant differences in performance ( p > 0.05). Our data support the concept of PRV surveillance based on oral fluid samples tested by an indirect gE ELISA.